Inter-individual variability in right ventricle adaptation after an endurance race. (July 2016) - Sanz de la Garza, María; Grazioli, Gonzalo; Bijnens, Bart H; Pajuelo, Carolina; Brotons, Daniel; Subirats, Enric; Brugada, Ramon; Roca, Emma; Sitges, Marta
Background: Right ventricle (RV) dysfunction has been described in athletes after endurance races. We aimed to understand and characterize the RV response to endurance exercise, the impact of individual variability and the effects of the amount of exercise. Methods and results: Echocardiography was performed in 55 healthy adults at baseline and after a three-stage trail race: short (14 km; n = 17); medium (35 km; n = 21); and long (56 km; n = 17). Standard and speckle tracking echocardiographic assessment of the RV was performed with global and separate analysis of the RV basal (inflow) and apical regions. Although no change was observed in the short distance runners, the RV systolic deformation decreased significantly ( p < 0.05) after both the medium length and long races (Δ% RV global strain −7.6 ± 20.1 and −8.7 ± 21.8, respectively) with significant RV dilatation (Δ% RV volume +10.6 ± 9.9 and +15.3 ± 12.8, respectively). The RV basal segment made a major contribution to stroke volume during exercise, showing larger increases in size and strain compared with the apex. Various patterns of RV adaptation to exercise, ranging from increases in both RV segmental strains and sizes to an insufficient increase in size and a decrease in strain, were identified; this individual variability was not correlated with prior training. Conclusion: An acute RV impairment was demonstrated after a trail-running race and was related to the amount of exercise. A high inter-individual variability was observed. Differences in RV adaptation patterns were independent of prior training, suggesting the influence was due to other individual factors.